Dinamika Diplomasi Pos: Kemitraan Pos Indonesia dengan Universal Postal Union (UPU) dalam Perspektif Hubungan Internasional - Pohan, Aplida Lisarah; Darmawan, Wawan Budi (Global and Policy Journal of International Relations, 2024)
The partnership between PT Pos Indonesia and the Universal Postal Union (UPU) in the context of international relations reflects the application of the liberalism paradigm. Liberalism, with its basic assumptions such as interdependence, mutual gains, and the belief in interdependence, provides a foundation for explaining the dynamics of international cooperation. In the context of the Pos Indonesia-UPU partnership, diplomacy is a key element that facilitates dialogue, negotiation, and agreement to achieve common goals. Institutional liberalism also plays a role in the creation of international regimes to strengthen cooperation. The research methodology uses a descriptive approach with a focus on the analysis of the impact of diplomacy, trade, and global stability of the partnership. Literature studies and policy analysis support the collection of primary and secondary data. The results of the study show that the Pos Indonesia-UPU partnership is not only about postal services but also reflects economic, global security, and technological development impacts in line with liberal principles. Challenges and barriers, such as improving service quality and competitiveness, can be overcome with investment and strong relationships with UPU. The liberal guide to innovation and progress is reflected in technological development and improved service quality. This partnership is an example of how liberalism shapes interactions between countries in the era of globalization, providing a positive contribution to diplomacy, economic growth, global security, and the development of postal services.Keywords: Universal Postal Union (UPU), PT. Pos Indonesia, LiberalismKemitraan antara PT Pos Indonesia dan Universal Postal Union (UPU) dalam konteks hubungan internasional menggambarkan penerapan paradigma liberalisme. Liberalisme, dengan asumsi dasar seperti saling ketergantungan, keuntungan bersama, dan keyakinan pada interdependensi, menjadi landasan dalam menjelaskan dinamika kerjasama internasional. Dalam kaitannya dengan kemitraan Pos Indonesia-UPU, diplomasi menjadi elemen kunci yang memfasilitasi dialog, negosiasi, dan kesepakatan untuk mencapai tujuan bersama. Liberalisme institusional turut berperan dalam penciptaan rezim internasional untuk memperkuat kerjasama. Metodologi penelitian menggunakan pendekatan deskriptif dengan fokus pada analisis dampak diplomasi, perdagangan, dan kestabilan global dari kemitraan tersebut. Studi literatur dan analisis kebijakan mendukung pengumpulan data primer dan sekunder. Hasil penelitian menunjukkan bahwa kemitraan Pos Indonesia-UPU tidak hanya mengenai layanan pos tetapi juga menggambarkan dampak ekonomi, keamanan global, dan pengembangan teknologi sesuai prinsip liberalisme. Tantangan dan hambatan, seperti peningkatan kualitas layanan dan daya saing, dapat diatasi dengan investasi dan hubungan yang kuat dengan UPU.  Panduan liberalisme untuk inovasi dan kemajuan tercermin dalam pengembangan teknologi dan peningkatan kualitas layanan. Kemitraan ini menjadi contoh bagaimana liberalisme membentuk interaksi antarnegara di era globalisasi, memberikan kontribusi positif dalam diplomasi, pertumbuhan ekonomi, keamanan global, dan pengembangan layanan pos.Kata Kunci: Universal Postal Union (UPU), PT. Pos Indonesia, LiberalismeDOI: https://doi.org/10.33005/jgp.v12i01.4321